Trans Jatim Bus Service Innovation in Encouraging Mobility and Local Economic Growth in Bangkalan Regency - Asrifia Ridwan; Mohamad Haerudin; Nurimansyah Setivia Bakti (Ilomata International Journal of Social Science, 2026)
This study examines the innovative Trans Jatim bus service corridor 5 in promoting mobility and local economic growth in Bangkalan Regency. This topic is important considering the role of public transportation in supporting inter-regional connectivity and impacting the strengthening of the local economy. This study examines the contribution of innovative bus services to public mobility and regional economic growth. The novelty of this research lies in its approach that not only views transportation as a means of mobility but also as a strategic instrument of economic development, which has not been studied in depth in the context of Bangkalan Regency. This research method is descriptive qualitative with a case study approach and analyzed using Rogers' diffusion of innovation theory. The findings show that Trans Jatim bus services provide affordable, accessible, and modern facilities that have been positively evaluated by the public. Through Rogers' diffusion of innovation theory, the process of adopting this service involves the stages of knowledge, persuasion, decision, implementation, and confirmation. Most people accept this innovation due to cost and time efficiency, although there is resistance from traditional transportation drivers who are economically impacted. The success of this service improves the local economy and spurs sustainable innovation for the welfare of the people of Bangkalan Regency.